2007
DOI: 10.1002/mrc.2038
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the anomeric configuration in carbohydrates by longitudinal cross‐correlated relaxation studies: application to mono‐ and disaccharides

Abstract: The role of cross-correlated relaxation between the anomeric proton chemical shift anisotropy (CSA) and its dipolar relaxation with nearby proton on the longitudinal relaxation in mono- and disaccharides at two magnetic field strengths has been investigated and shown to directly report the identity of their anomeric configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It has been reported that CSA/DD CCR is an important relaxation mechanism that is manifested by multiplet asymmetries in NMR inversion-recovery experiments where the monitoring pulse angle is small. 28 The anomeric configuration of ribonucleosides 64 as well as that of hexopyranoses 65 have been pseudorotation wheel corresponds to a puckering amplitude ϕm varying linearly from 0° to 60°. The energy scale is in kcal•mol −1 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that CSA/DD CCR is an important relaxation mechanism that is manifested by multiplet asymmetries in NMR inversion-recovery experiments where the monitoring pulse angle is small. 28 The anomeric configuration of ribonucleosides 64 as well as that of hexopyranoses 65 have been pseudorotation wheel corresponds to a puckering amplitude ϕm varying linearly from 0° to 60°. The energy scale is in kcal•mol −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The H R 2 simulation was performed using a 1 H CSA of 5 and 10 ppm and assuming an axially symmetric tensor (Z ¼ 0). The CSA value of 10 ppm is representative for an amide proton (45,46), whereas the value of 5 ppm is representative for a sugar anomeric proton (47,48). Again the contribution of CSA to the F R 2 and H R 2 are monotonic functions with t c and thus can be used for studying ligand binding.…”
Section: Figurementioning
confidence: 99%